Ureum and Creatinine Levels of Kidney Failure Patients Pra and Post Hemodialysis in Jayapura General Hospital Papua - Herlando Sinaga; Rini Prastyawati; Rivie Joan Pretty Tompodung; Beby Syahputra Surbakti; Sulistianingsih Sulistianingsih (Jurnal Sains dan Kesehatan, 2023)
Kidney failure is a worldwide health problem seen from the increase in incidence, prevalence, and the level of morbidity. Indonesia is one country with high rates of kidney failure. The purpose of this research was to determine the description of the results of urea and creatinine levels in patients with kidney failure before and after hemodialysis. The population used in this study was all renal failure patients who would carry out hemodialysis at the Jayapura Regional General Hospital (RSUD). The number of samples in this research is 30. The method of examining urea and creatinine used is the photometry method. This research was conducted from 10 May to 10 June 2018. To determine the levels of urea and creatinine before and after hemodialysis, the average value of the results of the examination was calculated and the results of the average urea level before hemodialysis 53.37 mg/dl and the average yield were obtained. Average after hemodialysis 18.83 mg/dl. The results of the average creatinine level of patients before 12.25 mg/dl and the average results after hemodialysis were 43.63 mg/dl. The results of the examination showed that there were no significant differences and that the results remained high. This research concluded that there was no significant difference between the examination of urea and creatinine levels before hemodialysis and after hemodialysis.